(untitled) (ModaPalavra e-periódico, 2025)
This research aims to propose recommendations for the design of bra for climacteric women usage in the workplace. The present research was conducted with 10 women in the climacteric age who were actively working; and three different data collection tools were applied: a questionnaire, the usability test of the OIKOS methodology aimed at two types of bras available in the Brazilian market, and a semi-structured interview. The questionnaire results elucidated the climacteric women’s preferences regarding the use and purchase of bras. Bras of the traditional and triangular styles were tested and received good scores in usability evaluation; the interview helped to clarify some issues pertinent to bras and usability testing. It was concluded that there is still room for the improvement of the design of climacteric women bras, making it possible to achieve the objective of this research and contributing to make the bra more suitable for the body and women’s activities at climacteric age.